ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN PEMBIAYAAN PADA BANK ACEH SYARIAH - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
This study aims to analyze the effect of third party funds, inflation, Non-Performing Financing, and Capital Adequacy Ratio on the distribution of Bank Aceh Syariah financing. The type of data used in this study is secondary data using monthly data for 4 years time series, from 2016 to 2019. The analytical method used is multiple linear regression using the Eviews analysis tool. The results showed that third party funds and capital adequacy ratios had a positive and significant effect on the distribution of financing, non-performing financing had a negative effect on the distribution of financing, while inflation had no effect on the distribution of financing at Bank Aceh Syariah.